A chip antenna in LTCC for UWB radios - Sun, Mei (2010)
The correspondence presents a chip antenna for ultrawideband (UWB) radios. The chip antenna is realized with a simple radiating element and small ground plane in low temperature cofired ceramic (LTCC) technology. The chip antenna has size 17 x 8 x 0.8mm3 and achieves impedance bandwidth from 3.75 to 10.45 GHz and gain from -2 to 2.3 dBi over this frequency band. The measured radiation patterns are presented and small group-delay variations are found at the UWB frequencies from 3.1 to 10.6 GHz.